Answer:
Step-by-step explanation:
The first two steps are for the purpose of eliminating fractions. Doing so results in 4(2x - 5) = 9(x - 2), which is to be solved for x.
Perform the indicated multiplication, obtaining:
8x - 20 = 9x - 18.
Then combine like terms: -2 = x, or
x = -2.
To complete the formal check, substitute -2 for x in the first equation. This results in:
(1/3)(-4 - 5) = (3/4)(-2 -2), or
-3 = -3
... which is obviously true.
Answer:
Step-by-step explanation:
length=1 m
base of triangle=10 m
height=5m
volume= 1/2×10×5×1=25 m cube.
slant height l=√(5²+5²)=√50=5√2
slant surface area=2[5√2×1]=10√2
area of front and back=2×1/2(10×5)=50
total surface area=50+10√2≈50+14.14≈64.14 m²
Answer:
All the exponents in the algebraic expression must be non-negative integers in order for the algebraic expression to be a polynomial. As a general rule of thumb if an algebraic expression has a radical in it then it isn't a polynomial
so no its not.
Answer:
x = -26
Step-by-step explanation:
Multiply both sides by the lowest common multiple of 4 and 3, which is 12.
3(x+2) = 4(x+8)
3x + 6 = 4x + 32 --- distribute the 4 and 3
6 = x + 32 --- subtract 3x from both sides
-26 = x --- subtract 32 from both sides
x = -26
Polygon ABCD goes through a sequence of rigid transformations to form polygon A′B′C′D′. The sequence of transformations involved is a reflection across the _Y-axis _, followed by a reflection across the line _y=-x__.